Same but different: space, time and narrative. (22nd January 2013) - Bansel, Peter
Abstract In this paper, I give an account of the ways in which narratives and identities change over space and time. I give an account of a mobile and changing human subject, one who does not simply express or represent her‐ or himself through narrative, but is constructed and reconstructed through narrative. I draw on Paul Ricoeur's concepts of 'narrative identity', which refers to the role of narrative in the formation and expression of identities, and 'refiguration', which refers to the ways in which both narratives and identities change over time. I work with extracts from narrative interviews in order to demonstrate the ways in which this might help us understand how narratives and identities change across space and time and also consider what this might mean for pedagogy and the practice of literacy/ies.